Komunikasi Visual Pada Bumper Acara Televisi (Analisis Semiotika Peirce pada Acara “Sarah Sechan” Di Net TV) - Rinkapati Swatriani (Universitas Mercu Buana, 2019)
Image formation in a television program not only through the content of the program itself but the show can also be through visual communication design that emerged during the program. One is Opening Break Bumper or better known as the bumper. Bumper is the opening animation that appears before starting a television program with a duration of 5-30 seconds. Bumper can be information to viewers about the type and characteristics as well as imaging or visualizing the concept of identity programs.In this study, the authors will focus on the visualization contained in the bumper in the program talk show